Rhetorical Tools in Multimodal Copywriting Texts - Ivanova, Iva (Media and Language, 2023)
The article is focused on two main aspects of copywriting texts – multimodality and rhetoric in order to outline the theoretical framework of these concepts and demonstrate their role as a tool for creating effective communicative messages. The analysis provided grounds for the following conclusions: The communicative effectiveness of multimodal copywriting texts directly depends on the correct combination of rhetorical tools with the other components of the multimodal text; taking into account the characteristics of the audience; the achievement of synchronicity between expressiveness and comprehensibility, between informativeness and emotionality within the text. The rhetorical tools commented in the article, combined with a methodological approach that takes into account the multimodal nature of copywriting texts, can draw guidelines for creating effective communicative models applicable in all spheres of modern communication.
Keywords: copywriting; multimodality; rhetoric; multimodal discourse